‘Let’s move on, please’: trust and employment relations in early-stage start-ups - Coelho, J. V. (Journal of Entrepreneurship and Innovation in Emerging Economies, 2020)
In Portugal, an evolving start-up hype has been promoted in recent years, presenting the country as an emergent European entrepreneurial hub, a rising start-up nation. In this context, less laudatory perspectives, focused on analysing labour relations or employment creation effects, are scarce or not particularly visible. In order to address this specific analytical dimension, this article conceives a start-up as a temporary organisational form, arraying temporariness not only as an organisational attribute, but a specific interaction condition that moulds employment relations established between startuppers and entrepreneurs. Analytical work is anchored in in-depth interviews and direct observation data, collected during a 12-month longitudinal study, carried out in one of the most successful start-ups created or operating in Portugal. A narrative is used as an empirical illustration of observed temporariness effects and three employment relation-specific attributes are discussed as aspects that should be inform public funding endorsement decisions: the prevalence of task-focus managerial arrangements; low levels of trust and institutionalised reciprocity; short-lived social relations and conflict deprioritisation.